2014
DOI: 10.1002/hyp.10378
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of high‐resolution specific conductance‐based end‐member mixing analysis and a graphical method for baseflow separation of four streams in hydrologically challenging agricultural watersheds

Abstract: Quantifying the relative contributions of different sources of water to a stream hydrograph is important for understanding the hydrology and water quality dynamics of a given watershed. To compare the performance of two methods of hydrograph separation, a graphical program [baseflow index (BFI)] and an end‐member mixing analysis that used high‐resolution specific conductance measurements (SC‐EMMA) were used to estimate daily and average long‐term slowflow additions of water to four small, primarily agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 32 publications
(70 reference statements)
1
40
0
1
Order By: Relevance
“…Cumulative Q BF-GHS and BFI GHS values were greater than Q BF-MEAS and BFI MEAS , respectively at 8 of the 12 sites. This finding is consistent with that of Kronholm and Capel (2014), who reported that GHS estimates of baseflow were greater than CMB estimates of baseflow in a stream draining an irrigated watershed in Washington that has a single extended ($5 months) high flow season, similar to that of a snowmelt-dominated hydrograph. Cumulative Q BF-GHS deviated most from Q BF-MEAS at the Dolores River sites (116-370% difference) and at GUN1 (70% difference, Table 5), where Q BF-GHS and BFI GHS were greater than Q BF-MEAS and BFI MEAS , respectively.…”
Section: Comparison Of Baseflow Estimatessupporting
confidence: 93%
“…Cumulative Q BF-GHS and BFI GHS values were greater than Q BF-MEAS and BFI MEAS , respectively at 8 of the 12 sites. This finding is consistent with that of Kronholm and Capel (2014), who reported that GHS estimates of baseflow were greater than CMB estimates of baseflow in a stream draining an irrigated watershed in Washington that has a single extended ($5 months) high flow season, similar to that of a snowmelt-dominated hydrograph. Cumulative Q BF-GHS deviated most from Q BF-MEAS at the Dolores River sites (116-370% difference) and at GUN1 (70% difference, Table 5), where Q BF-GHS and BFI GHS were greater than Q BF-MEAS and BFI MEAS , respectively.…”
Section: Comparison Of Baseflow Estimatessupporting
confidence: 93%
“…This may be insufficient to characterize systems with more complex or diverse hydrologic compartments or components (such as interflow or subsurface stormflow, movement of soil moisture, macropore flow) or with human modification (including diversions, dams, point sources and sinks, artificial drainage, and others) (Bazemore and others, 1994;Cartwright and others, 2014;Freeze, 1974;Klaus and McDonnell, 2013;Sanford and others, 2012;Vasconcelos and others, 2013). In some of these cases, multiple components may need definition, possibly using multiple tracers in an end-member mixing analysis (Genereux and others, 1993;Hooper and others, 1990;Kronholm and Capel, 2015).…”
Section: Limitations Of Hydrograph Separationmentioning
confidence: 99%
“…Water moves vertically to drains on the timescale of hours to days and laterally on the timescale of hours to months. Kronholm and Capel (2014) demonstrated that hydrograph separation methods, specifically the method of Wahl and Wahl (1995), can be used to describe slowflow and fastflow moving to a stream dominated by drainflow. The slowflow component describes water moving through the subsurface in areas far from the actual drains.…”
Section: Dmentioning
confidence: 99%
“…The thick, black line follows the behavior of sediment in a hydrologic setting where fast flowpaths are an important component of total streamflow, at least for part of the year. As an example, fastflow to Granger Drain in central Washington occurs when excess irrigation water is present on the landscape (Kronholm and Capel, 2014). Irrigation water is relatively abundant as snowmelt from the Cascade Mountains.…”
Section: Agricultural Activity Decision Tree As An Organizing Toolmentioning
confidence: 99%